THE INFLUENCE OF BIOTHIN ON GROWTH AND DEVELOPMENT OF BACTERIA LACTOBACILLUS PLANTARUM - Bondarchuk, Natalia; Reshetniak, Liudmila (Proceedings of National Aviation University (archive), 2018)
Objective: the aim of the study was to study the effect of biotin on the vital activity of lactic acid bacteria. Methods: a study of the effect of vitamin H on lactic acid bacteria Lactobacillus plantarum probiotic "Flactonia" was carried out in a periodic culture on selective nutrient media: MPC and cabbage. Biotin was added at a concentration of 5 mg/L to the media to stimulate the growth of Lactobacillus plantarum. It was used nutrient media (MRS and cabbage media) without growth promoter as a control. The study included the investigation of the dynamics of accumulation of bacteria Lactobacillus plantarum. To achieve this goal, sampling was carried out within 60 hours. The determination of biomass, active acidity and kinetic parameters of crop growth was carried out every 6 hours. Such kinetic parameters of bacteria growth as the rate of exponential growth (μ, h-1), constant of fission rate (V, h-1), generation time (g, hour). Isolation of lactic acid microorganisms was carried out by the method of multiseries dilutions. Incubation was carried out for 2-3 days at a temperature of 37 ° C. The number of colonies was counted by the last three dilutions, in which the growth of lactic acid bacteria was observed.The pH was determined potentiometrically using a membrane pH meter. Bacterial biomass was determined by nephelometric method. The optical density of the suspension was measured at 590 nm. The amount of biomass was expressed in mg of dry cells per mL of medium. A calibration curve for the dependence of the optical density of the culture fluid on biomass was used for the calculation. Results and discussion: the effect of the biotin stimulator (vitamin H) on vital activity, biomass accumulation and cultivation parameters of lactic acid bacteria Lactobacillus plantarum is investigated in the article. The results of the research indicate that when the biotin was introduced into the cabbage medium and the MRS medium, the cell division constant increases and the generation time decrease. In these media with a growth stimulator, the amount of biomass increased by 76% in cabbage medium and 50% in MRS compared to control. The number of colony-forming units (CFU) in the cabbage medium was 42%, and in the MRS medium was 28% higher than in the control (without biotin).